Lifting D-instanton zero modes by recombination and background fluxes - Blumenhagen, Ralph; Weigand, Timo (Arxiv, 2007)
We study the conditions under which D-brane instantons in Type II orientifold compactifications generate a non-perturbative superpotential. If the instanton is non-invariant under the orientifold action, it carries four instead of the two Goldstone fermions required for superpotential contributions. Unless these are lifted, the instanton can at best generate higher fermionic F-terms of Beasley-Witten type. We analyse two strategies to lift the additional zero modes. First we discuss the process of instantonic brane recombination in Type IIA orientifolds. We show that in some cases charge invariance of the measure enforces the presence of further zero modes which, unlike the Goldstinos, cannot be absorbed. In other cases, the instanton exhibits reparameterisation zero modes after recombination and a superpotential is generated if these are lifted by suitable closed or open string couplings. In the second part of the paper we address lifting the extra Goldstinos of D3-brane instantons by supersymmetric three-form background fluxes in Type IIB orientifolds. This requires non-trivial gauge flux on the instanton. Only if the part of the fermionic action linear in the gauge flux survives the orientifold projection can the extra Goldstinos be lifted.
Gesehen am 09.01.2018